Multifunctional Detection Sensor and Sensitivity Improvement of a Double Solenoid Coil Sensor - Laihao Ma; Zhiwei Xu; Hongpeng Zhang; Weiliang Qiao; Haiquan Chen (Micromachines, 2019)
A multifunction detection sensor for hydraulic oil contaminants based on a microfluidic chip is proposed, which consists of double solenoid coils and a straight microchannel. The inductance detection model of metal particles and capacitance detection model of nonmetal particles are constructed theoretically. In order to further improve detection sensitivity, experiments of effects of silicon steel sheets on the sensitivity of detection are carried out. Experimental results show that the silicon steel sheets can significantly improve the detection sensitivity of metal particles. The inductance amplitude and signal-to-noise (SNR) of iron particles ranging from 60−130 μm and copper particles ranging from 120−180 μm can be increased by at least 7.0−2.4 and 4.5−2.0 times, respectively. We demonstrate the successful detection of 30 μm iron particles and 90 μm copper particles using double solenoid coils with silicon steel sheets. In capacitance detection experiments, the silicon steel sheets can improve the sensitivity of capacitance detection, but the improvement effect is not obvious. We demonstrate the successful detection of 140 μm water droplets and 240 μm bubbles using double solenoid coils with and without silicon steel sheets. The capacitance amplitude and SNR of detecting water droplets ranging from 140−150 μm and bubbles ranging from 240−250 μm can be increased by 37.4−21.9% and 18.5−8.0% using double solenoid coils with silicon steel sheets, respectively.